2023
DOI: 10.3389/fnut.2023.1092781
|View full text |Cite
|
Sign up to set email alerts
|

Associations of adherence to Mediterranean-like diet pattern with incident rosacea: A prospective cohort study of government employees in China

Abstract: BackgroundDespite of growing evidence on gastrointestinal comorbidities of rosacea, there was a lack of literatures regarding the role of diet on rosacea.ObjectivesTo investigate the relationship between adherence to a Mediterranean-like diet pattern and the risk of incident rosacea.MethodsThis was a prospective cohort study of government employees aged >20 years conducted between January 2018 and December 2021 from five cities of Hunan province of China. At baseline, participants completed a food frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…While the MD is generally known to be beneficial for health and conditions such as diabetes, cancer, and cardiovascular disease [42,43], the data from this study suggest additional advantageous effects on facial inflammatory dermatoses. This supports recent findings of a negative correlation between acne and the adherence to a MD [44], as well as a reduced incidence of rosacea with adherence to a MD [39]. Thus, adhering to a MD appears to be beneficial for both acne and rosacea.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While the MD is generally known to be beneficial for health and conditions such as diabetes, cancer, and cardiovascular disease [42,43], the data from this study suggest additional advantageous effects on facial inflammatory dermatoses. This supports recent findings of a negative correlation between acne and the adherence to a MD [44], as well as a reduced incidence of rosacea with adherence to a MD [39]. Thus, adhering to a MD appears to be beneficial for both acne and rosacea.…”
Section: Discussionsupporting
confidence: 89%
“…The food items reported to be beneficial for both the AG and RG can be classified as a Mediterranean diet (MD), characterized by a high consumption of vegetables, legumes, oily fish, olive oil, nuts, and only moderate intake of meat, cheese, and alcohol [39][40][41]. While the MD is generally known to be beneficial for health and conditions such as diabetes, cancer, and cardiovascular disease [42,43], the data from this study suggest additional advantageous effects on facial inflammatory dermatoses.…”
Section: Discussionmentioning
confidence: 99%
“…The MD is based on a regular intake of olive oil as the primary source of fat and high consumption of fruits, vegetables, and grains, while allowing a moderate intake of white meat, fish and wine, and restricting the consumption of sugary products and red meat [ 27 , 28 ]. Research has suggested that adherence to the MD may reduce the risk of cardiovascular disease (CVD), type 2 diabetes mellitus, metabolic syndrome, dementia, rosacea, psoriasis, and hidradenitis suppurativa [ 29 35 ]. These health benefits have been attributed to the effects of the MD on insulin sensitivity, endothelial function, blood lipids, and inflammatory and oxidative stress [ 36 ].…”
Section: Introductionmentioning
confidence: 99%